A Randomized Study to Compare the Effects of Once-Weekly Dulaglutide Injection and Once-Daily Glimepiride on Glucose Fluctuation of Type 2 Diabetes Mellitus Patients: A 26-Week Follow-Up. (30th April 2019) - Li, Huiqin; Xu, Xiaohua; Wang, Jie; Kong, Xiaocen; Chen, Maoyuan; Jing, Ting; Zhang, Zhiying; Yin, Guoping; Liu, Xiaomei; Hu, Yun; Ye, Lei; Su, Xiaofei; et al.
Abstract : Objective . To evaluate the effects of once-weekly dulaglutide injection and once-daily glimepiride on glucose fluctuation in patients with type 2 diabetes mellitus (T2DM) using the Continuous Glucose Monitoring System (CGMS). Methods . A total of 23 patients with T2DM were randomly assigned into two groups for 26 weeks: the dulaglutide group (n = 13 ) and the glimepiride group (n = 10 ). 72-hour CGMS was applied to all patients: before and after the treatment. General clinical data were collected and measured, such as fasting blood glucose (FBG), glycosylated hemoglobin (HbA1c), tumor necrosis factor- α (TNF- α ), 8- iso -prostaglandin F2 α (8- iso -PGF2 α ), and interleukin-6 (IL-6). Results . HbA1c of the dulaglutide group was reduced from8.38 ± 0.93 % to6.68 ± 0.73 % after the treatment (P < 0.05 ); similarly, it was reduced from7.91 ± 0.98 % to6.67 ± 0.74 % (P < 0.05 ) in the glimepiride group. The levels of serum 8- iso -PGF2 α, TNF- α, and IL-6 all decreased significantly in both groups after treatment, and there was no significant difference found between the two groups (P > 0.05 ). The Mean Blood Glucose (MBG) of the two groups declined significantly after therapy (P < 0.05 ). However, the Standard Deviation of Blood Glucose (SDBG) decreased significantly only in the dulaglutide group (from2.57 ± 0.74 mmol/L to1.98 ± 0.74 mmol/L, P < 0.05 ). There were no significant changes of Mean Amplitude of Glycemic Excursion (MAGE) and Absolute Means of Daily Difference (MODD) after treatment in both groups. Furthermore, no statistically significant difference was found between the two groups in MBG, SDBG, MAGE, and MODD (P > 0.05 ). The percentage time (PT) (>10 mmol/L and 3.9-10 mmol/L) of the two groups was significantly changed after the treatment (P < 0.05 ). However, this was not seen in thePT < 3.9 mmol/L after the treatment (P > 0.05 ). Conclusion . Once-weekly dulaglutide injection has the same effectiveness as daily glimepiride on lowering blood glucose and decreasing oxidation stress and inflammation and is more effective in controlling glucose fluctuation as compared with glimepiride. This trial is registered with ClinicalTrials.govNCT01644500 .